ChemInform Abstract: Diastereoselective Synthesis of Cyclopentanone‐Fused Spirooxindoles by N‐Heterocyclic Carbene‐Catalyzed Homoenolate Annulation with Isatilidenes. Issue 14 (March 2016) - Patra, Atanu; Bhunia, Anup; Yetra, Santhivardhana Reddy; Gonnade, Rajesh G.; Biju, Akkattu T.
Abstract: The approach involves the generation of homoenolate intermediates which undergo a formal [3+2] annulation reaction.